Serendipitous observation of a coronal mass ejection during the total solar eclipse of 14 December 2020 - Abramson, Guillermo (2021)
We report observations of the total solar eclipse of 14 December 2020, during which a coronal mass ejection was seen to propagate. A comprehensive set of photographs covering a high dynamic range of exposure enabled characterization of its dimensions. Displacement of the front can be seen during the few minutes of totality.